Evaluation of Atrial Conduction Times, Epicardial Fat Thickness and Carotid Intima-Media Thickness in Patients With Ankylosing Spondylitis - Sabri Onur ÇAĞLAR; İsmail BOYRAZ and Fatma ERDEM and Selma YAZICI and Hilal ÇAĞLAR and Bünyamin KOÇ and Emrah ÇAĞLAR and Mehmet YAZICI (Archives of Rheumatology, 2016)
Objectives: This study aims to determine the relationship between atrial electromechanical delay (EMD), carotid intima-media thickness (CIMT), and epicardial fat thickness (EFT) in ankylosing spondylitis (AS), which has a complicated inflammatory nature. Patients and methods: The study population included 42 consecutive patients with AS (28 males, 14 females; mean age 39.3±8.5 years; range 22 to 60 years) and 40 healthy subjects as controls (24 males, 16 females; mean age 37.2±8.7 years; range 22 to 60 years) (p>0.05). All patients underwent a standard tissue Doppler echocardiography to assess the left ventricular diastolic dysfunction, atrial EMD, CIMT, and EFT. All values were compared between the groups. Results: Interatrial (29.5±5.8 ms vs. 17.9±5.3 ms) left and right intraatrial EMD (18.2±4.6 ms and 11.7±3.5 ms vs. 11.9±3.2 ms and 7.1±3.2 ms, respectively) intervals were longer in AS patients than in healthy controls (all p<0.001). Left and right CIMT (0.50±0.11 mm and 0.44±0.06 mm vs. 0.51±0.11 mm and 0.43±0.04 mm, respectively) and EFT (0.73±0.15 cm and 0.63±0.07 cm) values were higher in AS patients than in healthy controls (all p<0.01). Conclusion: To our best knowledge, this is the first report evaluating the atrial EMD, CIMT, and EFT values together in AS patients. As indicators of cardiovascular involvement, all parameters were higher in AS patients.